Recyclable l-glutamic acid-based polyester schiff base cross-linker for 3D printing applications - Kamble, Ganesh N.; Ghute, Aaditi P.; Asha, S. K. (ACS Applied Polymer Materials, 2026)
An l-amino acid-based polyester Schiff base cross-linker was developed from amine-functionalized polyester and biobased methacrylate vanillin. Vanillin, one of the few biobased and aromatic compounds readily available on an industrial scale, has recently garnered significant attention from the polymer community. The l-amino acid-based polyester Schiff base cross-linker (P3) was synthesized by condensing the aldehyde group of methacrylate vanillin with the amine group of the l-glutamic acid polyester. This polymeric cross-linker was used in resin formulations consisting of isobornyl acrylate as a reactive diluent and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide as the photoinitiator for digital light processing (DLP) three-dimensional (3D) printing. The resulting 3D-printed parts exhibited good mechanical properties, with a Young's modulus of 1.5 GPa, and high thermal stability, with a T max of 410 degrees C. The chemical degradability of the 3D-printed materials was demonstrated in a mixture of tetrahydrofuran and diethylene triamine (1:1) at 80 degrees C for 48 h. The reusability of the recovered resin was demonstrated by adding fresh methacrylate vanillin and photoinitiator, followed by 3D printing using a DLP 3D printer. The 3D-printed parts produced from the recycled resin retained substantial mechanical properties, with a Young's modulus of 1.39 GPa, and thermal stability, with a T max of 390 degrees C.
Keywords: 3D printing; chemical degradation; covalent adaptable network; l-glutamicacid; Vanillin